Vistas for geodesy in the new millennium : IAG 2001 Scientific Assembly Budapest, Hungary, September 2-7, 2001 - IAG 2001Scientific Assembly (2001 : Budapest, Hungary); Adam, Jozsef, 1950-; Schwarz, Klaus-Peter (New York, NY : Springer-Verlag, 2002)
26